Aquatic phytoremediation: Novel insights in tropical and subtropical regions - Eugenia Judith Olguín Palacios; Gloria Sánchez Galván (Pure and Applied Chemistry, 2010)
An overview of the state of the art in phytofiltration of nutrients and heavy metals (HMs) from wastewaters using tropical and subtropical plants in constructed wetlands (CWs) and lagoons is presented. Various mechanisms to remove these pollutants are discussed, in regard to three different types of systems: surface flow constructed wetlands (SFCWs), sub- surface flow constructed wetlands (SSFCWs), and lagoons with floating plants. Only recent reports at laboratory, pilot and full scale, especially in tropical regions, are discussed. Most of the experiences around the world have shown that these systems are efficient and high re- moval percentages have been reported for both, nutrients and metals. However, there are still several unsolved or partially understood issues. Long-term studies at the mesocosms or large scale, in order to gain a full insight of the various mechanisms occurring in each system, are required. The understanding of the fate or compartmentalization of the pollutants in these complex artificial ecosystems, especially in the case of HMs, will permit us to establish the frequency of harvesting and the advantages of the use of specific species. The huge bio- diversity that is commonly found in tropical and subtropical regions represents a challenge for finding new species with outstanding characteristics for tolerance to toxic and recalcitrant pollutants or to extreme environmental conditions, such as high temperature or salinity.